Perlindungan Hukum Terhadap Pekerja Lanjut Usia Berdasarkan Hukum Ketenagakerjaan (Kasus Pengemis Online dalam Konten Mandi Lumpur di Tiktok) - Muhamad Farudin (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines the increasing number of elderly individuals working in the informal sector and the exploitation risks they face, particularly through social media. According to data from BPS, there has been a rise in active elderly workers, with most employed in the informal sector. Indonesia's Labor Law does not provide specific protections for elderly workers, making them vulnerable to exploitative actions, such as the